2022
DOI: 10.3892/ol.2022.13612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrin α7 on cell proliferation, invasion, apoptosis and the PI3K/AKT pathway, and its association with clinicopathological features in endometrial cancer

Abstract: Targeting integrin α7 (ITGA7) suppresses malignant progression of several types of cancer, including tongue squamous cell carcinoma, hepatocellular carcinoma and non-small cell lung cancer, while the effect of its knockdown on cell function and its association with clinicopathological features in endometrial cancer (EC) is unclear. The present study aimed to investigate this issue. ITGA7 was knocked down by short-interfering (si)RNA in Ishikawa and RL95-2 cells followed by western blotting and reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…For instance, Ming et al detected ITGA7‐expressing cells in most esophageal squamous cell carcinoma tissues but not in corresponding nontumor tissues 31 . Lv et al and Liang et al found that the ITGA7 was mainly expressed in tumor tissues compared with paired adjacent tissues 40,41 . However, in papillary thyroid carcinoma, ITGA7 was mainly expressed in nontumor tissues compared to tumor tissues 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Ming et al detected ITGA7‐expressing cells in most esophageal squamous cell carcinoma tissues but not in corresponding nontumor tissues 31 . Lv et al and Liang et al found that the ITGA7 was mainly expressed in tumor tissues compared with paired adjacent tissues 40,41 . However, in papillary thyroid carcinoma, ITGA7 was mainly expressed in nontumor tissues compared to tumor tissues 42 .…”
Section: Discussionmentioning
confidence: 99%
“…IHC staining results showed that ITGA7 was expressed predomi- was mainly expressed in tumor tissues compared with paired adjacent tissues. 40,41 However, in papillary thyroid carcinoma, ITGA7…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the L1CAM [386], HSD17B2 [387], GRP (gastrin releasing peptide) [388], FABP4 [389], SOX6 [390]. MMP12 [391], APOD (apolipoprotein D) [392], LAG3 [393], CST1 [394], FLT1 [395], DHCR24 [396], PRL (prolactin) [397], WNT5A [398], TIMP3 [399], CD24 [400], LHCGR (luteinizing hormone/choriogonadotropin receptor) [401], MMRN1 [402], CD4 [403], ADAMTS5 [404], ADAMTS1 [405], PADI2 [406], MARK1 [407], KL (klotho) [408], PLAU (plasminogen activator, urokinase) [409], SOX8 [410], CRABP2 [411], PTPRD (protein tyrosine phosphatase receptor type D) [412], EPCAM (epithelial cell adhesion molecule) [413], IRX2 [414], SEMA3B [415], CYP1A1 [416], PDGFD (platelet derived growth factor D) [417], LEPR (leptin receptor) [418], APOE (apolipoprotein E) [419], CASP1 [420], MGLL (monoglyceride lipase) [421], NID1 [422], ABCG2 [423], ACE (angiotensin I converting enzyme) [424], PGR (progesterone receptor) [425], HPSE2 [426], LMTK3 [427], ALPP (alkaline phosphatase, placental) [428], EGFL6 [429], CACNA2D3 [430], MCTP1 [431], HKDC1 [432], S100A4 [433], MACC1 [434], MMP3 [435], FGFR2 [436], IL33 [437], FOXC2 [438], ITGA7 [439], EFEMP1 [440], GATA6 [441], BHLHE41 [442], TCF21 [443], GDF10 [444], NKX3-1 [445], AKR1C3 [446], SGK1 [447], RAP1GAP [448], FLI1 [449], NOX4 [450], SERPINE2 [451], IGSF9 [452], IGF2BP1 [453], SALL4 [454], VDR (vitamin D receptor) [455], CELSR2 [456],...…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we identified an upregulated gene set responsible for lung development, which suggests that ZNF714 silencing may reduce cell potency. In our validation assays, we tested three downregulated genes with known oncogenic properties (Figure 6D), namely EFEMP2 [53,54], ITGA7 [55][56][57], and COL8A1 [58][59][60]. These genes participate in cell adhesion, extracellular matrix organization, cell proliferation, and anatomical structure morphogenesis (Figure 6B).…”
Section: Discussionmentioning
confidence: 99%